Dual-mandate of persons who serve as MPs and mayors at the same time - Zagorc, Saša (Lex localis, 2008)
The incompatibility of the function at the state and local levels is defined to prevent exercising a dual mandate and other forms of conflict of interest to secure self-government in local communities. The discussed positions of dual- or even triple-mandate officials are neither unconstitutional nor unlawful in themselves, yet they relate to die incompatibility of interest roles these dual-mandate or triple-mandate officials simultaneously play. The inability of the National Assembly to regulate the issue of the incompatibility of the function in accordance with the basic principles in the state (balance of powers, local self-government autonomy, representative democracy) leads us to the conviction that, for the time being, the parliamentary lobby power is too great, whereas the political culture of the public is too weak to prevent the further steps of the legislator. An important aspect of rhe incompatibility of the function lies in the fact that individuals should be aware that performing the multiple functions, obtained in elections, is not a privilege, but it is a commitment and duty to perform die functions well and with dedication. The paradox is that an individual who is aware of this does not need any rules on the incompatibility of the function at all.
Keywords: delitev oblasti; lokalna samouprava; nezdružljivost funkcij; podžupani; poslanci; Slovenija; župani